2021
DOI: 10.1097/ccm.0000000000005383
|View full text |Cite
|
Sign up to set email alerts
|

Use of Antifibrinolytics in Pediatric Life-Threatening Hemorrhage: A Prospective Observational Multicenter Study

Abstract: OBJECTIVES: To assess the impact of antifibrinolytics in children with life-threatening hemorrhage. DESIGN: Secondary analysis of the MAssive Transfusion epidemiology and outcomes In Children study dataset, a prospective observational study of children with life-threatening bleeding events. SETTING: Twenty-four children’s hospitals in the United States, Canada, and Italy. PATIENTS: Children 0–17 years old who received greater than 40 mL/kg of total blood products over 6 hours or were transfused under act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
44
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 55 publications
0
44
0
Order By: Relevance
“…Second, the study by Spinella et al (1) did not consider the heterogeneity of each hospital. Because this was an observational study, hospital-related factors, such as severity of hemorrhage, ICU care, and mortality rates in patients that are critically ill, might vary at each participating hospital.…”
Section: To the Editormentioning
confidence: 99%
“…Second, the study by Spinella et al (1) did not consider the heterogeneity of each hospital. Because this was an observational study, hospital-related factors, such as severity of hemorrhage, ICU care, and mortality rates in patients that are critically ill, might vary at each participating hospital.…”
Section: To the Editormentioning
confidence: 99%
“…33 In a secondary analysis of the population receiving antifibrinolytics, they found that TXA or epsilon-aminocaproic acid was independently associated with improved 6-and 24-hour survival in bleeding children. 32 This study included 449 patients from 24 centers with bleeding for any reason, 207 had traumatic injury, and 54 received TXA. After adjusting for Pediatric Risk of Mortality score in a Cox proportional hazard model, TXA decreased 6-hour mortality with an odds ratio of 0.29 (95% CI, 0.09-0.93).…”
Section: Pediatric Trauma Hemorrhagic Shock Consensus Conferencementioning
confidence: 99%
“…To review, three of the five pediatric studies evaluated indicated an association of TXA with improved mortality. 28,31,32 Two of these were in combat populations and adjusted for injury severity. 28,31 The other, the MATIC trial, was a civilian prospective study and adjusted for relevant confounders.…”
Section: Pediatric Trauma Hemorrhagic Shock Consensus Conferencementioning
confidence: 99%
“…Mortality in children with traumatic hemorrhagic shock is between 36% and 50% based on recent studies 3,4 . Recent retrospective and prospective observational studies indicate that resuscitation practices (limiting crystalloid, appropriate blood product ratios, use of whole blood, and tranexamic acid use) can dramatically reduce morbidity and mortality in children with traumatic hemorrhagic shock 5–9 . Because of these alarming statistics, resuscitation and hemostatic strategies are a key target for standardization and subsequent investigation.…”
mentioning
confidence: 99%
“…3,4 Recent retrospective and prospective observational studies indicate that resuscitation practices (limiting crystalloid, appropriate blood product ratios, use of whole blood, and tranexamic acid use) can dramatically reduce morbidity and mortality in children with traumatic hemorrhagic shock. [5][6][7][8][9] Because of these alarming statistics, resuscitation and hemostatic strategies are a key target for standardization and subsequent investigation. However, clinical trial design surrounding this topic would be very difficult because of not only the lack of standardization in resuscitation approaches, transfusion strategies, utilization of hemostatic monitoring, and adjuncts but also the lack of agreed upon critical definitions and common data elements for study.…”
mentioning
confidence: 99%